IMPLEMENTASI PROGRAM MENGHAFAL AL-QUR’AN JUZ 30 DI SMP WAHID HASYIM MALANG - Dewi Kurniawati; Nur Hasan; Zuhkhriyan Zakariya (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study aims to determine the implementation of the memorization program juz 30of the Qur'an at Wahid Hasyim Junior High School Malang. The focuses studied are 1)program planning, 2) program implementation, and 3) program evaluation systems.in this study used is a qualitative method with the type of case study. The procedure fordata collection was carried out using the observation method, namely observation, theinterview method which is a method of collecting by using oral questions and answerswith sources, and the documentation method, namely looking for data on mattersrelated to the research. The research results obtained are: 1) planning the program tomemorize the Qur'an juz 30 is carried out by determining the person in charge,determining the memorization material and determining the time allocation; 2) theimplementation of the memorization program of the Qur'an juz 30 there are severalmemorization methods that are used but do not yet have a lesson plan, the supervisingteacher provides a target for memorizing deposits in every meeting, in theimplementation of the memorization program there are of course some obstaclesfaced, namely from class conditions, time allocation , and students' ability tomemorize; and 3) the evaluation system for the memorization program of the AlQur'anjuz 30 supervising teachers has a list of memorization deposit checklists byassessing how the quality of memorization is according to the specified criteria andthe results will be used in the form of a rote report card at the end of the semester.